From wells to wealth? Government transfers and human capital - Julio Acuna; Lenin H. Balza; Nicolas Gomez-Parra (Inter-American Development Bank (IDB), 2022)
To study the causal impact of oil royalties on human capital, we exploit quasi-experimental variation arising from a law in Ecuador that transfers resources to municipalities regardless of their oil-producing status. We find that royalties increase the likelihood of students completing primary and secondary education. Students reaching high school are also more likely to pass and excel on the exit exam. Furthermore, schools are more likely to remain open, increase their size, and become more road-accessible. However, the likelihood of students pursuing higher education decreases as they face steeper opportunity costs when labor demand increases.
Keywords: I25; O13; O15; Q32; Q35; 330; natural resources; oil royalties; transfers; human capital; Ecuador